Some Aspects of Radiation Induced Damage to Enzymes Using α- amylase As A Model - Azhar A.A.L-AL Obaydy (College of Education for Pure Sciences, 2005)
a-amylase enzyme was isolated and purified from wheat flour (abena zero). Different aqueous enzyme solutions were exposed to gamma radiation in order to investigate the behavior of this enzyme toward ionization radiation under various experimental conditions. Radiolysis of aqueous oxygenated a-amylase solutions led to a significant increase in activity to many folds as a function of dose. Addition of Cu(D ),Ni(D ),Zn(D ) complexes and MgCl2 to a-amylase un-irradiated solutions also increase enzyme activity. This phenomenon indicates clearly a conformation change in enzyme structure. Or on other word, partial unfold regions in enzyme molecule, could be created by radiation attack or/and by interactions of metal complexes or MgCl2 with enzyme molecules, as a result of disruption of weak bonds such as H-banding or hydrophobic bonds. Radiolysis of enzyme solutions containing Cu(D ),Ni(D ) and Zn(D ) complexes and MgCl2 has been investigated. Radiolysis of N2 -saturated enzyme solutions did not show any increase in activity, but a gradual decrease was observed on proceeding irradiation, This clears up the role of oxygen in enzyme radiosensitization. Lysine and Tyrosine amino acids were selected as model for amino acids with aliphatic and aromatic residues respectively. The effect of metal complexes on the rate of decay of organic peroxides formed on these amino acids, by irradiation was studied. Addition of irradiated Lysine solutions in presence of Cu (alanine)2 complex lo un-irradiated a -amylase solution caused enzyme deactivation . Kinetic study was applied on the decay of organic peroxides. In brief, these studies provide information that the activity of native enzyme contributes to only small part of the whole capacity of enzyme activity. This reflects a fact that most sites involved in catalytic activity of the enzyme are not involved, at least, directly in enzyme activity.